"To Err Is Human" but Disclosure Must be Taught: A Simulation-Based Assessment Study. Issue 2 (April 2018) - Crimmins, Ashley C.; Wong, Ambrose H.; Bonz, James W.; Tsyrulnik, Alina; Jubanyik, Karen; Dziura, James D.; Dodge, Kelly L.; Evans, Leigh V.
Abstract : Introduction: Although error disclosure is critical in promoting safety and patient-centered care, physicians are inconsistently trained in its practice, and few objective methods to assess competence exist. We used an immersive simulation scenario to determine whether providers with varying levels of clinical experience adhere to the disclosure safe practice guidelines when exposed to a serious adverse event simulation scenario. Methods: This was a prospective cohort study with medical students, junior emergency medicine (EM) residents (PGY 1–2), senior EM residents (PGY 3–4), and attending EM physicians participating in a simulated case in which a scripted medication overdose resulted in an adverse event. Each scenario was videotaped and scored by two expert raters based on a 6-component, 21-point disclosure assessment instrument. Results: There were 12 participants in each study group (N = 48). There was good interrater reliability (κ = 0.70). Total scores improved significantly as the level of training increased: medical student = 10.3 (2.7), PGY 1–2 = 12.3 (6.2), PGY 3–4 = 13.7 (3.2), and attending physicians = 12.8 (3.7) ( P = 0.03). Seventy-five percent of participants did not address preventing recurrence of the error. Fifty-six percent offered no apology or only offered it with prompting from the patient; only 23% offered an apology with the initial disclosure. Conclusions: We demonstrated suboptimal adherence to best practices guidelines for error disclosure when providers are assessed in an immersive simulation setting. Despite a correlation in performance of medical error disclosure with increased physician experience, this study suggests that healthcare providers may need additional training to comply with safe practice guidelines for disclosure of unanticipated adverse events.